2005
DOI: 10.4049/jimmunol.174.12.7753
|View full text |Cite
|
Sign up to set email alerts
|

Restricted STAT5 Activation Dictates Appropriate Thymic B versus T Cell Lineage Commitment

Abstract: The molecular mechanisms regulating lymphocyte lineage commitment remain poorly characterized. To explore the role of the IL7R in this process, we generated transgenic mice that express a constitutively active form of STAT5 (STAT5b-CA), a key downstream IL7R effector, throughout lymphocyte development. STAT5b-CA mice exhibit a 40-fold increase in pro-B cells in the thymus. As documented by BrdU labeling studies, this increase is not due to enhanced B cell proliferation. Thymic pro-B cells in STAT5b-CA mice sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
6
33
1
1
Order By: Relevance
“…Expression was analyzed using quantitative real-time PCR (qRT-PCR). Consistent with our previous observation (Goetz et al, 2005) progenitor B cells from Stat5b-CA mice show increased expression of Pax5 relative to wild-type progenitor B cells (Goetz et al, 2005; Fig. 5 A).…”
Section: Ar Ticlesupporting
confidence: 79%
See 1 more Smart Citation
“…Expression was analyzed using quantitative real-time PCR (qRT-PCR). Consistent with our previous observation (Goetz et al, 2005) progenitor B cells from Stat5b-CA mice show increased expression of Pax5 relative to wild-type progenitor B cells (Goetz et al, 2005; Fig. 5 A).…”
Section: Ar Ticlesupporting
confidence: 79%
“…To determine if the leukemic cells were proliferating more rapidly than wild-type pro-B and pre-B cells, we injected mice displaying visible signs of leukemia with BrdU. In both Stat5b-CA restore B cell development to near normal levels (Goetz et al, 2005). We crossed Stat5b-CA x Pax5 +/ mice to IL-7r / mice to generate Stat5b-CA x Pax5 +/ x IL-7r +/ or Stat5b-CA x Pax5 +/ x IL-7r / mice.…”
Section: Ar Ticlementioning
confidence: 99%
“…Thus, the regulation of Jak levels represents another mechanism by which Notch mediates its selective inhibitory effect on B-cell development. Consistent with our findings, it has been shown that the expression of a constitutively active form of STAT5, which can bypass the need for activating cytokines and Jaks, increases the numbers of B cells in the thymus (11).…”
supporting
confidence: 80%
“…For these studies, we made use of transgenic mice that express a constitutively active form of STAT5b (STAT5b-CA) (21,26,31). Expression of STAT5b-CA is regulated by a compound promoter element consisting of the lck proximal promoter with the E enhancer inserted into it.…”
Section: Stat5 Activation Restores Cd4mentioning
confidence: 99%